The Evaluation of the Undergraduate Studies Program and The Educational Process in Heis Operating in Uncertainty Conditions: The Case of The Department of Business Administration of the Technological Educational Institute (T.E.I) of Thessaly-Greece - Sdrolias, Labros; Gkountroumpi, Evangelia; Koffas, Stefanos; Škodová Parmová, Dagmar; Aspridis, Georgios; Rolínek, Ladislav; Dvořáková Líšková, Zuzana; Belias, Dimitrios (International Organization Center of Academic Research, 2016)
The Greek Higher Educational Institutes (HEIs) constitute great bureaucratic organizations that display a series of peculiar functional and production features, as for example close dependence upon the given at times governmental power, geographically scattered branches, fragmentation of similar departments, absence and incoherence of the cognitive fields of several departments with the real needs and the available comparative advantages of the geographical areas in which they operate, established and completely oldfashioned production and transmission of knowledge and skills which bear only a very small relation to the contemporary entrepreneurship, innovation, and the job market in general. Thus, lately, under the burden of the country’s tragic economic situation and the demands on the part of the Troika for the reduction of the cost of education, as well as of the newly-shaped international educational conditions, there has been attempted a systematic restructuring of the Greek HEIs, on the basis of the application of a specific governmental plan, known under the name of “Athena Plan. The role of Greek Tertiary Education seems to be fruitless, since a series of serious or even unsurpassed problems come up, as for instance the inadequate function of the Institutions due to the significant reduction in state funding, insufficient transmission of knowledge and skills because of the forced transformation of laboratory courses into theoretical subjects, severe cutbacks in the fees of the educational and administrative staff, purposeful delays in the academic development of the educational staff, etc. Within the turmoil of these conditions and of the continuous insecurity, the Human Resources of these Institutions make conscientious efforts towards the direction of meeting the multiple educational needs.
Keywords: HEIs; Uncertainty Conditions; Studies Program (Curriculum) and Educational Process Evaluation; Technological Educational Institute (T.E.I) of Thessaly; Greece